2002
DOI: 10.1080/1463137022000032655
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-monetary Trade in Russian Transition

Abstract: The appearance of significant non-monetary trade in the Russian transition of 1992-98 has been differently interpreted by analysts and observers. Some have seen barter as a symbol of passive resistance to reforms while others have blamed reformist policies for its development. We argue that non-monetary trade is best understood as a natural response of companies to market imperfections remaining from Soviet times. We provide an overview of market institutions that existed at the onset of the transition and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Accordingly, the 1998 crisis has shifted the balance between the Russian real economy and the financial sector to the benefit of the former. As some economists argue, it was the network of barter and non-monetary trade that not only helped Russia face the tremendous challenges of the financial liberalisation and speculation and sustain relative socio-economic stability; the 'virtual' economy also accounts for much of the post-crisis recovery in the Russian industry (Moody, 1999;Ivanenko and Mikheyev, 2002). In what follows, the paper evaluates the role of the non-monetary economy in Russia's evolution to an open capitalist system.…”
Section: Downloaded By [Chulalongkorn University] At 18:29 27 Decembementioning
confidence: 98%
“…Accordingly, the 1998 crisis has shifted the balance between the Russian real economy and the financial sector to the benefit of the former. As some economists argue, it was the network of barter and non-monetary trade that not only helped Russia face the tremendous challenges of the financial liberalisation and speculation and sustain relative socio-economic stability; the 'virtual' economy also accounts for much of the post-crisis recovery in the Russian industry (Moody, 1999;Ivanenko and Mikheyev, 2002). In what follows, the paper evaluates the role of the non-monetary economy in Russia's evolution to an open capitalist system.…”
Section: Downloaded By [Chulalongkorn University] At 18:29 27 Decembementioning
confidence: 98%
“…Because the retail trade and provision of consumer services were, however, mainly monetary, individual households had to react to the new situations either by lowering their standard of living (Clarke 2000) or by selling the goods received at the workplace on streets and highways or in marketplaces. It is not our intention to review the large research literature on barter here (see for example Seabright 2000a; Ivanenko and Mikheyev 2002;Woodruff 2000). It suffices to say that barter was not only an economic but also a social phenomenon operating through social relations (Seabright 2000b: 8).…”
Section: Barter: a Transitory Phenomenon Of Exchangementioning
confidence: 99%
“…According to Ivanenko and Mikheyev (2002;see also Clarke 2000: 178-9), in the background of barter there were the structural weaknesses and bottlenecks of the socialist system. The Soviet economy had built a massive industrial production system which was connected to an inflexible and one-sided distribution, trade, and banking network.…”
Section: Barter: a Transitory Phenomenon Of Exchangementioning
confidence: 99%
“…Humphery (2000a) mentioned that post-soviet barter was unique because there were no other examples of large economies that relied heavily on barter mechanisms (see Chapter 3 and Seabright 2000). Ivanenko and Mikheyev (2002) concluded that barter appeared as a result of the structural weakness of the soviet system. Companies that were unable to pay suppliers or to pay salaries in cash had to offer goods or raw material or other forms of non-monetary payments.…”
Section: Social Network In Soviet and Transition Economiesmentioning
confidence: 99%